The Dilemma of Religious Tolerance: Levinasian Critique and Proposal - Hambali, Radea Yuli. A (International Journal of Nusantara Islam, 2023)
Religious tolerance is a critical issue in pluralistic societies such as Indonesia. Without tolerance, the expressions of beliefs can lead to fanaticism, conflict, and hostility that negatively impact social security and stability. This article addresses the dilemma of religious tolerance by exploring and connecting the concept of â€œthe Otherâ€ in Emmanuel Levinasâ€™ thought as an ethical subject who requires protection and respect for the individual with the discussion of tolerance indicators in the context of religious moderation. This qualitative study employs a literature review method, with data collected through literature review and analyzed descriptively using Emmanuel Levinasâ€™ philosophical perspective. The results indicate that religious tolerance in the framework of religious moderation, as found in Emmanuel Levinasâ€™ thought, entails the recognition and respect for the identity of the â€œOtherâ€. The â€œOtherâ€ is an ethical subject with the right to live free from discrimination and oppression. In the framework of tolerance, the â€œOtherâ€ is not merely allowed to exist and differ but necessitates the growth of respect and appreciation through fair and respectful treatment of those who are different. From Levinasâ€™s viewpoint, the practice of religious tolerance must be carried out by considering the concept of ethical relationships between individuals and â€œThe Other.â€ Religious tolerance manifests ethical responsibility to recognize and respect the existence of others with different religions and beliefs. This article proposes that Levinasian philosophy can provide a useful critique and proposal for the dilemma of religious tolerance in pluralistic societies